Anticoagulants of primary haemostasis - Kössler, J.; Steigerwald, U.; Walter, U. (Hämostaseologie, 2009)
Inhibition of platelet function plays an important role in the treatment and secondary prevention of cardiovascular or cerebrovascular ischemic diseases. Established antiplatelet agents use different pharmacological targets for this role. Acetylic salicylic acid achieves a reduction of thromboxane A2 formation by inhibition of COX-1. Ticlopidin or clopidogrel are ADP-P2Y12 receptor antagonists. Tirofiban, abciximab or eptifibatid are used for the inhibition of the glycoprotein IIb/IIIa receptor which is activated at the surface of platelets preceding the final step of their aggregation. The mechanism of dipyridamole is based on the inhibition of adenosine uptake and of phosphodiesterase-5.Efforts are made to improve antiplatetelet therapy with the aim to find agents with favorable clinical outcome and lower bleeding risk. Current clinical studies focus on a new generation of ADP receptor antagonists (prasugrel, cangrelor and ticagrelor) as successors of ticlopidin and clopidogrel after coronary arterial interventions. Developments using platelet targets different from established drugs are thrombin receptor antagonists (like SCH530348) or thromboxane receptor antagonists (like S18886/terutroban) in patients with cerebrovascular events. Results from recent experimental studies could lead to new strategies for antiplatetelet therapy (like inhibition of GP Ib receptor, GP VI receptor, platelet-leukocyte interaction, factor XII and others) in the future.
Keywords: Antiplatelet agent; acetylic salicylic acid; ADP receptor antagonist; secondary prevention